Fuzzy Logic Controller Design for Intelligent Air-Conditioning System - Ahamed, N. U.; Zahari, Taha; Ismail, Mohd Khairuddin; Rabbi, M. F.; Rahaman, S. A. M. Matiur; Sundaraj, Kenneth (IEEE, 2016)
Inefficient air cooling systems may cause of wasting energy in a great amount specially in the urban area. Being the most popular cooling system, air-conditioners have been used in domestic usage as well as in industrial applications. However, the unintelligent nature of such cooling system gives rise to excess energy consumption which causes a huge problem in the current energy hungry world. In this paper, we present design of a fuzzy logic controller for the intelligent air-conditioning system. The performance of the controller is also simulated. The proposed controller has the adaptive nature to control fan and compressor speed which leads to reducing power consumption. Also, the system controls the operation mode to retain the healthy oxygen level and humid condition of the indoor environment.